2004
DOI: 10.1021/jp0470795
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Optical Property of Silicon Oxide Layer Coated Semiconductor Gallium Nitride Nanowires

Abstract: Quasi one-dimensional GaN-SiO(2) nanostructures, with a silicon oxide layer coated on semiconductor GaN nanowires, were successfully synthesized through as-synthesized SiO(2) nanoparticles-assisted reaction. The experimental results indicate that the nanostructure consists of single-crystalline wurtzite GaN nanowire core, an amorphous SiO(2) outer shell separated in the radial direction. These quasi one-dimensional nanowires have the diameters of a few tens of nanometers and lengths up to several hundreds of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…The well-known characteristic absorption bands, similar to those published elsewhere, 4,7 were observed from the FTIR data (not shown) near 453, 812 and 1083 cm 1 . In addition, the XRD data (not shown), consistent with the results of Zhang et al, 8 indicated that the SiO 2 powders were amorphous. The particle diameter estimated from SEM micrographs was between 1 and 3 µm.…”
Section: Resultssupporting
confidence: 89%
“…The well-known characteristic absorption bands, similar to those published elsewhere, 4,7 were observed from the FTIR data (not shown) near 453, 812 and 1083 cm 1 . In addition, the XRD data (not shown), consistent with the results of Zhang et al, 8 indicated that the SiO 2 powders were amorphous. The particle diameter estimated from SEM micrographs was between 1 and 3 µm.…”
Section: Resultssupporting
confidence: 89%
“…In the case, if semiconductors comprise the core and shell, the core-shell motif has permitted enhanced photoluminescence, improved stability against photochemical oxidation, enhanced processibility, and engineered band structures [1][2][3]. They are expected to have great potential applications for photoelectronic nanodevices, and electronic transportation [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The depolarization ratios were checked with a reference sample of liquid CCl 4 . The pinhole of the confocal microscope was closed at about 140 micron, which corresponded to a focal volume of about 1 micron cube, limiting significantly As reported by various authors for thin films 15,16 and for bundles of nanowires, 12,17 GaN that crystallizes in the hexagonal Wurtzite-type structure belongs to the space group (C 4 6v ) and has two formula units per primitive cell. According to the factor group analysis, the Raman active modes are 1A 1 (x 2 + y 2 , z 2 ) + 1E 1 (xz, yz) + 2E 2 (x 2 À y 2 , xy) while 2B 2 modes are silent.…”
Section: Polarized Raman Microscopy Of Single Nanostructuresmentioning
confidence: 89%
“…The parameters A, B, C, D, E, can be determined assuming that the depolarization ratio r tends towards zero in resonant conditions and that one element of the polarizability tensor is dominant. Finally we can measure 6 spectra that are functions of the five hF i,j,k i order parameters as shown in (16,17).…”
Section: Biaxial Systemsmentioning
confidence: 99%